Nurses Work Stress Levels with Caring Nurses Behavior - Dian Sari; Maisharoh (Professional Evidence-based Research and Advances in Wellness and Treatment, 2024)
All over the world, health workers, including nurses, experience job stress. A study conducted on nurses at Lancang Kuning Hospital Pekanbaru found that many things can cause them to experience high work stress. These include fatigue and psychological distress caused by a non-ideal working environment. (Djamaluddin, 2022). To determine the relationship between nurses' caring behavior and their level of job stress, thi s quantitative study will use a descriptive correlational approach. All nurses working in the hospital are included in the population of this study. A sample size of 42 nurses will be taken using a stratified random sampling technique to ensure that the sample comes from various work units of the hospital, such as the emergency department, intensive care unit, and general care unit. Of the 42 nurses surveyed, only 38.1% (16 people) reported experiencing mild job stress, while 61.9% (26 people) reported experiencing moderate job stress. No nurses reported experiencing significant job stress, according to Table 1. Nurses demonstrated both good and poor caring behaviors, as shown in Table 3. 28.5% of twelve nurses showed good behaviors, and 71.5% of thirty nurses showed poor behaviors. Nurses with mild job stress showed good caring behavior (23.81%) compared to nurses with poor caring behavior (14.29%). In contrast, nurses with work stress more often showed poor caring behavior (57.14%) than nurses with good caring behavior (4.76%). The results of this study show that reducing nurses' job stress has a negative correlation with their caring behavior; nurses with lower levels of job stress tend to perform better caring behavior.